Pemanfaatan Limbah Aki dan Komponen Elektronik sebagai Sumber Energi Listrik Ramah Lingkungan - Junaidi Junaidi; Agus Riyanto; Gurum Ahmad Pauzi; Iqbal Firdaus (Jurnal Pengabdian Pada Masyarakat, 2021)
UTILIZATION OF ACCU WASTE AND ELECTRONIC COMPONENTS AS AN ENVIRONMENTALLY FRIENDLY ELECTRICAL ENERGY SOURCE. This community service is a form of community development activity in the utilization of Accu waste and electronic components as an alternative energy source for mini-inverters. The mini-inverter module is made using the Joule Thief method. This method is able to increase low electric power from a 1.5-volt battery source into AC alternating current that can turn on LED lights. The service activity will be carried out in Hajimena Village, Natar District, South Lampung Regency in August 2020. This community service activity was attended by 32 participants. Each service participant has been fostered and guided about the process of making mini-inverter modules from waste batteries and components that are no longer used so that they are ready to use and suitable for use and of economic value. The components used in the manufacture of mini-inverters are all obtained from components from AKI and used electronic components as alternative energy sources. With this activity, it is hoped that the partner community will understand how to utilize waste that is difficult to decompose into ready-to-sell goods.